The Incidence and Nature of Everyday Sexism in Filipino Women's Lives: Comparisons of Heterosexual and Sexual Minority Women's Experiences - Torre, Beatriz A. (Review of Women's Studies; Vol 31 No 1 (2021): Review of Women's Studies Volume XXXI, Number 1 (2021), 2023)
Everyday sexism, which encompasses expressions of gender prejudice and displays of gender-discriminatory behavior in people's daily lives, is a pervasive and impactful experience for many women. Most of the existing research on everyday sexism has been conducted in Western contexts, and has not explored possible differences among sub-groups of women, such as differences across sexual orientation. Drawing on insights from intersectionality theory and ambivalent sexism theory, the present research used an online survey to examine the incidence and nature of everyday sexism in the lives of heterosexual and sexual minority Filipino women and investigate how the intersection of gender and sexual orientation shape these experiences. Results showed an average frequency of one to two sexist events a day in women's lives. Regardless of sexual orientation, the three most commonly reported forms of everyday sexist events were (1) comments reflecting gender roles and stereotypes, (2) jokes about women or girls related to their gender, and (3) ogling. Sexual minority women reported significantly higher frequencies of certain types of sexist events under the categories of traditional gender roles and stereotypes and sexual objectification compared to heterosexual women. Qualitative data from an optional open-ended survey item also suggest generally negative reactions to experiences of harassment as well as differences in heterosexual and sexual minority women's evaluations of their experiences of benevolent sexism. Insights into the ways in which intertwining traditional ideologies of gender and sexuality give rise to these differences, as well as implications for further research about and efforts to challenge everyday sexism, are also discussed.